The model of lateral spinal cord hemisection. Part I. The technical, pathomorphological, clinical and experimental peculiarities - Vitaliy Tsymbaliuk; Volodymyr Medvediev; Vera Semenova; Nina Grydina; Yuriy Senchyk; Olga Velychko; Sergiy Dychko; Victoria Vaslovych (Ukrainian Neurosurgical Journal, 2016)
Relevance of the topic. A promising tool for restoring the spinal cord function is the application of tissue neuroengineering. The approbation of its techniques is possible on qualitative spinal cord injury models that makes the transplantation of solid neuroengineered matrices feasible.Objective. To optimize and test a model of lower thoracic rat’s spinal cord hemisection.Materials and methods. 2 groups of experimental animals: 1 — mature animals (3–6 months, n=40) and 2 — young animals (1 month, n=32), the injury — left-side spinal cord hemisection (LHS) at Т11 level; monitoring of hindlimbs’ function (BBB scale), pathomorphological study.Results. LHS provides simultaneous display of a slight, moderate and severe spinal cord injury (the correlates, respectively, are: the function deficit of a contralateral hindlimb [CH] and an ipsilateral hindlimb [IH] among the animals with better and worse recovery indicators). As of the 11th week of the observation a function indicator was 3,2±0,58 points under BBB scale and 5,31±0,79 (p<0.05) in group 2, which indicates a significant fullness of the intersection of all descending fibers. Mortality in group 1 at the stage of intervention and in the acute phase of trauma consists 25%, in the remote phase — 15%, including 5 percent of animals with bilateral injury. At full bilateral intersection mortality within 10 days with relevant conditions of detention comprises 100 percent.Conclusion. LHS model is technically simple, easy to be reproduced, has low mortality under the condition of deep ipsilateral spinal cord function deficit, provides for three simultaneous options of spinal cord injury, is adapted for testing the neuroengineering tools.